2015
DOI: 10.1097/phm.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review of AbobotulinumtoxinA in Clinical Trials for Adult Upper Limb Spasticity

Abstract: ObjectiveThe aim of this study was to elucidate clinical trial efficacy, safety, and dosing practices of abobotulinumtoxinA (ABO) treatment in adult patients with upper limb spasticity (ULS).MethodsA systematic literature review was performed to identify randomized controlled trials and other comparative clinical studies of ABO in the treatment of adult ULS published in English between January 1991 and January 2013. Medical literature databases (PubMed, Cochrane Library, and EMBASE) were searched, and a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…1,2 Botulinum toxin A (BoNT-A) is a first-line treatment for muscle overactivity in spastic paresis, [3][4][5] and coupling injections with neurorehabilitation may improve outcomes. [6][7][8] Although numerous studies have reported post-stroke or -TBI benefits of abobotulinumtoxinA (Dysport; Ipsen) on muscle tone 4,[9][10][11][12][13][14][15][16][17][18][19][20][21] and passive function 4,9,14,17 for up to 24 weeks after a single injection, its effects on active function remained uncertain. 3,4,19,21,22 Few studies have addressed the safety and efficacy of repeated BoNT-A injections and none have shown effects on active movement.…”
mentioning
confidence: 99%
“…1,2 Botulinum toxin A (BoNT-A) is a first-line treatment for muscle overactivity in spastic paresis, [3][4][5] and coupling injections with neurorehabilitation may improve outcomes. [6][7][8] Although numerous studies have reported post-stroke or -TBI benefits of abobotulinumtoxinA (Dysport; Ipsen) on muscle tone 4,[9][10][11][12][13][14][15][16][17][18][19][20][21] and passive function 4,9,14,17 for up to 24 weeks after a single injection, its effects on active function remained uncertain. 3,4,19,21,22 Few studies have addressed the safety and efficacy of repeated BoNT-A injections and none have shown effects on active movement.…”
mentioning
confidence: 99%
“…None of these studies provided joint‐specific outcomes associated with abobotulinumtoxinA dose. Despite our standardized protocol [20], our data likely reflect real‐world injections in that numerous different muscle and dose injection combinations were used, as in past studies [8,13,14,17,19].…”
Section: Discussionmentioning
confidence: 94%
“…Evidence‐based information on optimal dosing for clinical use is relatively sparse. Dosing is not interchangeable between different BoNT‐A products; therefore, improving our understanding of product‐specific dosing will minimize confusion among injectors and improve the quality of patient care [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These different treatment options are discussed in more detail in the guidelines in Table 2 and in other review papers. 32,[43][44][45] Financial and administrative barriers …”
Section: Treatment Optionsmentioning
confidence: 99%